Interpreter training programs versus the office of sworn translators and commercial interpreters in Brazil: a case study in the State of Ceará - Badaró de Athayde Prata, Ananda; Cruz Romão, Tito Lívio (Mutatis Mutandis. Revista Latinoamericana de Traducción, 2019)
In Brazil, almost all the state Commercial Boards select sworn translators and interpreters (tpics) by means of public tenders. However, there are no requirements for the applicants concerning previous qualification in translation/interpreting. According to Wyler (2003), since Colonial Brazil, public translation/interpreting has always been present in the country. Only in the 1950s, interpreting started to be an object of study in the field of Linguistics and, later, of Translation Studies. To classify particularly the field of interpreting, Mikkelson (2009), Pagura (2001) and Pöchhacker (2004) resort to different criteria, considering the contexts in which interpreting is performed and the interpreters’ working modes. With views of delineating the profile regarding sworn translators’ qualification in interpreting in the state of Ceará (Brazil), this work will outline a brief historical panorama of this profession in Brazil and its respective legislation. Next, the results of a questionnaire which was applied to sworn translators in Ceará with 17 questions about their working practice and professional qualification will be discussed. There was a high rate of answers: 62,26%. According to the data, 81,8% of the sworn translators do not hold any qualifications in interpreting, although 75,8% of them work as interpreters. As a whole, these results allow us to reflect upon which measures could be recommended concerning basic and/or continuing professional trainings that could help to change this reality.